Cooperative games as a pedagogical strategy for decreasing bullying in physical education: Notable changes in behavior - Oliveira, Lidiane Souza; De Oliveira, Welson Riceli Ferreira; Filho, Josué José de Carvalho [UNESP]; Borges, Célio José; De Oliveira, Glauber Lameira; De Oliveira, Talita Adão Perini; Da Silva, Vernon Furtado; Valentim-Silva, João Rafael (My University, 2017)
Problem: the bullying have a big prevalence among children around the word, especially in the school. Today, this behavior is associated to depression, low self esteem, and, including suicide, becoming a very important public heath problem. Objectives: to verify whether or not cooperative games are able to reduce bullying in Physical Education classes. Propose: a volunteer group of 240 individuals from two municipal schools in the capital and smaller city of Rondônia was selected, with a mean age of 9.89 + 0.42 years including both sexes. To verify the number of bullying incidents, the researchers observed five classes before and after an experimental intervention based exclusively on cooperative games, for 3 months in Physical Education classes lasting 60 minutes with two classes per week. The statistical treatment was descriptive through the mean and standard deviation and inferential by means of the “student t test” and a sensitivity of 5%. Results: occurrences of verbal aggression decreased by 85.7% and physical aggression decreased by 100%. Conclusions: cooperative games seem to reduce bullying in Physical Education classes suggesting that the cooperative games may be a strong tool to reduce the bullying.
Keywords: Bullying; Cooperative games; Physical education classeroom; Physical violence; Verbal violence